Soft Drink Advertisements and Evoked Nostalgia Among Consumers: An Empirical Study in India and Oman - Ambily AS; Mobin BABY; Sanjith SR; Ajith AM; Nivetha S; Krishna S RAJU (Communications of International Proceedings, 2024)
This study explores how soft drink advertisements create a sense of nostalgia among consumers. Nostalgia refers to the longing for or fond remembrance of the past. The research aims to measure the level of nostalgia customers feel after watching such advertisements. A questionnaire was developed to collect responses from people in different age groups and regions, specifically in Kerala, India, and Muscat, Oman. This research is relevant since it addresses a gap in the literature about how nostalgia works in advertising within Indian and Omani contexts. It highlights that evoking nostalgia can be an effective strategy for soft drink companies, especially in today’s market, where many consumers seek comfort and emotional connection. By creating advertisements that trigger fond memories, brands can foster stronger relationships with their customers and offer emotional relief to those experiencing stress or anxiety. The study uses descriptive, bivariate, regression, and CFA analyses to understand the impact of nostalgic advertisements on consumers. The findings reveal that these advertisements positively influence customers’ feelings, making them happy and encouraging them to purchase more products. Nostalgic ads also shape consumers’ attitudes toward the brand and prompt them to reflect on their past experiences.
Keywords: Nostalgia; Advertisement; consumer Behaviour; Soft Drinks